Participation of the MPCs in the European Research Area. Capacity building activities in MIRA Project - Rossano M.; Morini C.; El Fellah R. (Moving forward in the Euro-Mediterranean Research and Innovation partnership. The experience of the MIRA project, 2013)
Capacity building, based on ad-hoc training initiatives on EU instruments and policies, is essential to improve international cooperation and enhance quality and quantity of Mediterranean Partner countries’ participation in EU-funded projects. The final objective is to further enable scientists and institutions of Mediterranean Partner Countries to be key actors in the Euro-Mediterranean research and innovation partnership, while facing the main challenges of the years to come. Bottlenecks, proposed solutions and performed activities are illustrated and analysed.